Green Supply Chain Management and Ecological Impact Mitigation in East Kalimantan Mining - Rina Masithoh; Catur Kumala Dewi (International Conference on Economics, Management, Business, and Accounting, 2025)
This study examines the adoption of Green Supply Chain Management (GSCM) strategies within the mining sector of East Kalimantan, aiming to support a sustainable economic transition and mitigate ecological risks. Driven by the pressing need to address the severe environmental consequences of resource extraction, this research employs a descriptive qualitative methodology, utilizing primary data derived from a questionnaire distributed to 28 managerial respondents. Findings indicate robust corporate commitment to GSCM, particularly in high-compliance areas such as Environmental Management Systems and Reverse Logistics. Reverse logistics has been proven to be the most critical component for mitigating post-mining ecological liabilities. However, GSCM adoption faces structural inertia in Green Distribution and Energy Transition. The perceived benefits are primarily strategic (improved corporate image), with high uncertainty regarding direct economic quantification. The study highlights the necessity of deepening GSCM penetration into pre-mining planning and integrating environmental accounting to realize sustainability goals fully.